Fiesta fiasco [compact disc] - Paul, Ann Whitford (Live Oak Media, 2012)
When shopping for Culebra's birthday, Conejo convinces his friends Iguana and Tortuga to buy all the wrong presents. Includes a glossary of Spanish words used.